2018
DOI: 10.21608/jappmu.2018.39798
|View full text |Cite
|
Sign up to set email alerts
|

Transportation, Adaptive and Productive Performance of Transported Buffalo Herd in New Environment

Abstract: The study was carried out in El-Nobarya Station, Beheira Governorate and El-Nataf El-Kadeem Station, Kafr El-Sheikh Governorate. Twenty-two buffalo cows were included in the experiment. Animals were transported\d to El-Nobarya station to establish a buffalo herd in this station.The experiment included two stages, the first stage aimed to study the effect of transportation and the second stage aimed to study the effect of acclimatization in El-Nobarya station. Meteorological data were collected and recorded inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
(11 reference statements)
2
4
0
Order By: Relevance
“…In contrast, calves belong to WS type with high heat stress recorded the lowest reproductive parameters. These results are in accordance with many previous studies (Mohamed et al, 2017;Ibrahim et al, 2018;Omran and Hamdon, 2018;Omran et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In contrast, calves belong to WS type with high heat stress recorded the lowest reproductive parameters. These results are in accordance with many previous studies (Mohamed et al, 2017;Ibrahim et al, 2018;Omran and Hamdon, 2018;Omran et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
“…THI index still the best indicator for stress under natural environmental conditions. Additionally, any improvement in THI would be ideally beneficial as a basis for the continuous development of biological responses and the representation of the consequences of primary factors in energy exchange (Omran and Hamdon, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They also added that, if the skin surface temperature is below 35 °C, the temperature gradient between the core and skin is large enough for the animals to effectively use all routes of heat exchange. This agreement with Omran and Hamdon (2018). Shafie and Omran (2018) reported that buffalo under two different thermal artificial conditions had the total number of hair per cm2 (449.50 and 915.00 in a lab) (A at 40°C) and lab (B at 25°C), respectively.…”
Section: -Buffalo Skinsupporting
confidence: 85%
“…The significance of the increase of the respiration rater RRr/min under heat stress is that it enables the animals to dissipate the excess of body heat by vaporizing more moisture in the expired air, which accounts for about 30 % of the total heat dissipation HD°C (Omran et al,2017 and2019c, e). The processes of conduction convection and radiation are all dependent on a thermal gradient, thus as air temperature rises towards body temperature the thermal gradient is reduced and heat dispersion is less effective, in addition, the non-evaporative cooling will shift to evaporative cooling when the ambient temperature is equal or above body temperature as described by Khalifa (2003) & Omran and Hamdon (2018). The shade reduced death losses to 33 % and production losses of surviving cows to 50 % for cows without shadow (Hahn, 1981).…”
Section: -Housing Systemmentioning
confidence: 99%
“…Since, the processes of conduction convection and radiation are all dependent on thermal gradient, thus as air temperature rises towards body temperature the thermal gradient is reduced and heat dispersion is less effective, in addition the non-evaporative cooling will shift to evaporative cooling when ambient temperature equal or above body temperature as described by Khalifa (2003) and Omran and Hamdon (2018). The RR a good measures of core temperature and has been used by many investigators to detect the response of animal to the environmental conditions (air temperature & relative humidity).Also the significance of the increase of the respiration rate under heat stress is that it enables the animals to dissipate the excess of body heat by vaporizing more moisture in the expired air, which accounts for about 30 % of the total heat dissipation (Kundu andBhatnagar, 1980 andOmran et.…”
Section: Resultsmentioning
confidence: 99%